2010
DOI: 10.1007/s11695-010-0255-3
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Sleeve Gastrectomy—Radiological Assessment of Fundus Size and Sleeve Voiding

Abstract: No correlation was found between the estimated volume of the remaining gastric fundus and weight loss (%EBL) after LSG. Patients showing a rapid gastroduodenal transit of the CM achieved a better weight loss than patients with a slow voiding rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 27 publications
2
27
1
2
Order By: Relevance
“…Similar results were observed by Vidal et al in their study, where they measured the sleeve volume with upper gastro-intestinal series [8]. Pomerri et al measured the gastric fundus volume and found no correlation between the fundus volume and weight loss achieved up to 1 year postoperatively [11].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar results were observed by Vidal et al in their study, where they measured the sleeve volume with upper gastro-intestinal series [8]. Pomerri et al measured the gastric fundus volume and found no correlation between the fundus volume and weight loss achieved up to 1 year postoperatively [11].…”
Section: Discussionsupporting
confidence: 83%
“…There are hardly any studies evaluating pre-operative stomach volume and volume of stomach excised during LSG. Pomerri et al found no correlation between the volume of the residual fundus and percentage excess weight loss [11].…”
Section: Resultsmentioning
confidence: 96%
“…2, 3), is needed. Some studies reported that this might cause a reduced weight loss or weight regain [3]. Our results, along with some others, did not confirm these findings [24,33], showing that the presence of a fundic pouch did not significantly affect weight loss, and, if present, pouch volume was not correlated with BMI reduction.…”
Section: Discussioncontrasting
confidence: 97%
“…Current surgical approaches include restrictive, malabsorptive or combined restrictive/malabsorptive procedures [3]. Laparoscopic sleeve gastrectomy (LSG) was initially discovered as first-step surgery prior to a more complex procedure (Roux-en-Y gastric bypass or biliopancreatic diversion-duodenal switch [4]) to reduce the overall operative risk in super-obese or high-risk patients [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…This is also true after LSG where ghrelin levels are even lower due to complete extraction of gastric fundus [24,43]. Finally, while LRYGB is known to induce dumping syndrome due to accelerated transit of undigested chime through the GI tract, accelerated gastric emptying can also occur after LSG [28,35,44], which may add to weight loss mechanisms.…”
Section: Discussionmentioning
confidence: 99%